Diagnostic test of huffy coat smear with Gram staining at sepsis neonatorum. - Christina Kastanti Nugrahani,, Christina Kastanti Nugrahani, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Neonatal sepsis is known as a leading cause of neonatal morbidity and mortality. It is hard to diagnose clinically sepsis due to its nonspecific manifestations. Blood culture has been the gold standard for neonatal sepsis. Unfortunately, it takes time to get the result, it is costly, and it is not easily performed. Buffy coat smear with Gram stain in attempt to diagnose neonatal sepsis is less costly and easily performed.Objective: To know the diagnostic value of buffy coat smear with Gram staining to diagnose neonatal sepsis.Methods: This cross sectional study was carried out at the Maternal-Perinatal Installation of Dr. Sardjito Hospital, Yogyakarta, between October 131, 2003 to March 3111, 2004. The inclusion criteria was clini-cally sepsis neonates (0-28 days old). Neonates with blood disorder, congenital anomaly, or had got antibiotic previously were excluded from this study. The buffy coat smear with Gram staining was examined and than was blindly validated with blood culture.Result: There were 127 neonates enrolled in this study. Buffy coat smear with Gram stain to diagnose neonatal sepsis produced sensitivity 77% (95% Cl, 65-88), specificity 85% (95% Cl, 77-93), positive predictive value (PPV) 78% (95% Cl, 67-90), negative predictive value (NPV) 84% (95% Cl, 76-92), positive likelihood ratio 5,24 (95% Cl, 2,98-9,24), and negative likelihood ratio 0,3 (95% Cl, 0,16- 0,45).Conclusion: Buffy coat smear with Gram stain was sufficiently accurate as diagnostic test for neonatal sepsis. The diagnostic value of buffy coat is expected to be useful for clinicians to predict neonatal sepsis earlier and guide them in making decision for clinical management.Keywords: neonatal sepsis - diagnostic test - buffy coat - gram positive stainingÂ